Tales of the Tail and Sperm Head Aches : Changing concepts on the prognostic significance of sperm pathologies affecting the head, neck and tail - Chemes, Hector Edgardo (2012)
This article presents an update on the variable prognostic significance of different sperm pathologies in patients with severe male factor infertility due to morphology and motility disorders. Severe asthenozoospermia is one of the leading causes of male infertility as spermatozoa cannot reach the oocyte and/or penetrate normally. Identifying structural causes of sperm immotility was of great concern before the advent of intracytoplasmic sperm injection (ICSI), because immotility was the limiting factor in the treatment of these patients. In these cases, in vitro methods are used to identify live spermatozoa or stimulate sperm motility to avoid selection of non-viable cells. With these advances, fertilization and pregnancy results have improved dramatically. The identification of genetic phenotypes in asthenozoospermia is important to adequately inform patients of treatment outcomes and risks. The one sperm characteristic that seriously affects fertility prognosis is teratozoospermia, primarily sperm head and neck anomalies. Defects of chromatin condensation and acrosomal hypoplasia are the two most common abnormalities in severe teratozoospermia. The introduction of microscopic methods to select spermatozoa and the development of new ones to evaluate sperm quality before ICSI will assure that ultrastructural identification of sperm pathologies will not only be of academic interest, but will also be an essential tool to inform treatment choice. Herein, we review the differential roles played by sperm components in normal fertilization and early embryo development and explore how assisted reproductive technologies have modified our concepts on the prognostic significance of sperm pathologies affecting the head, neck, mid-piece and tail.